Translators’ tools offered by digital humanities: genre-related and sociolinguistic aspects - Więcławska, Edyta (Comparative Legilinguistics, 2026)
This paper focuses on significant role of digital tools in translators’ training. It is claimed that digital competences may be successfully developed, for example by working with language corpora that introduce us to markedly wider range of linguistic and extralinguistic information (context, generic profile). Presentation of specific cases is preceded by a short discussion on legal factors concerning translators’ competence requirements. It has been noted that the translation competence models has been evolving over years, which is due to changing market-related conditions and extending educational possibilities. It is also emphasised that developing digital competences in the population of translators and translation trainees constitutes a stable element of the translation competence requirement and it is stipulated by relevant legal regulations in many countries, whether explicitly or implicitly.